Consumption of energy drinks and their effects on sleep quality among medical students - Ranya Alshumrani; Bashayer Shalabi; Abdulsamad Sultan; Lamar Wazira; Sarah Almutiri; Azzam Sharkar (Journal of Family Medicine and Primary Care)
Background and Objectives: Energy drinks contain caffeine, which causes genuine concern among health professionals and authorities about their negative health effects. Their effect on sleep quality specifically was not well studied. In our study, we aim to assess the prevalence of energy drink consumption and its effect on the quality of sleep among Saudi medical students. Materials and Methods: A cross-sectional study was done on 260 medical students who were in their first till the sixth academic year at King Abdulaziz University Jeddah, Saudi Arabia. An online questionnaire was distributed as a Google form including demographics, the beverage questionnaire (BEVQ-15), and the Pittsburgh sleep quality index (PSQI). Results: Coffee was found to be the most favorite (56.5%) caffeinated beverage among medical students, 46.2% reported a sleep duration of 5 h, and 15% reported a sleep latency of more than 30 min. Also, 19.3% were found to have reduced sleep efficiency (less than 74%) and 82.6% used sleep medication once a week. Male students had a significantly higher mean frequency of drinking Energy & Sports drinks (Red Bull, code red, Gatorade, etc.) compared to females. Moreover, 74.6% of the medical students studied had poor sleep quality, with no relationship found between sleep quality and participant demographics, favorite caffeinated beverages, BEVQ-15 scale scores, or the frequency of energy drink consumption. In contrast, the PSQI and BEVQ-15 scores showed a significant positive correlation. Conclusion: Students at the university level should be educated on the causes of poor sleep quality and the effect of energy drinks on sleep quality. More research on a larger sample of Saudi university students is needed to determine the scope of the problem.